1999
DOI: 10.1074/jbc.274.20.13748
|View full text |Cite
|
Sign up to set email alerts
|

The Bell-shaped Ca2+ Dependence of the Inositol 1,4,5-Trisphosphate-induced Ca2+ Release Is Modulated by Ca2+/Calmodulin

Abstract: 1 is a second messenger used by many cell types to release Ca 2ϩ from internal stores (1). Cytosolic Ca 2ϩ has a bell-shaped effect on the IP 3 receptor (IP 3 R), with low concentrations stimulating the release and high concentrations inhibiting it (2-5). Calmodulin, a Ca 2ϩ -binding protein abundantly present in many cell types (6), binds to the modulatory region of the IP 3 R in a Ca 2ϩ -dependent way (7,8). Calmodulin also interacts with the IP 3 R in a Ca 2ϩ -independent way (9 -11), with one of the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 25 publications
9
59
0
Order By: Relevance
“…3A shows a dose-re- . This is in accordance with our previously obtained data in A7r5 cells (14). In contrast, the addition of MLCK peptide (1 or 10 M) had no effect on the EC 50 value for Ca 2ϩ release compared with the control condition.…”
Section: Cam-binding Peptide Derived From Mlck Decreases the Ip 3 Rsupporting
confidence: 82%
See 2 more Smart Citations
“…3A shows a dose-re- . This is in accordance with our previously obtained data in A7r5 cells (14). In contrast, the addition of MLCK peptide (1 or 10 M) had no effect on the EC 50 value for Ca 2ϩ release compared with the control condition.…”
Section: Cam-binding Peptide Derived From Mlck Decreases the Ip 3 Rsupporting
confidence: 82%
“…From the observation that the dissociation takes several minutes, it can be expected that the affinity is in the nanomolar or subnanomolar range. 3 -Previously, we have shown that adding exogenous CaM to permeabilized cells inhibited IICR (14,17). This inhibition is Ca 2ϩ -and IP 3 -dependent.…”
Section: Cam-binding Peptide Derived From Mlck Decreases the Ip 3 Rmentioning
confidence: 99%
See 1 more Smart Citation
“…CaM is a ubiquitously expressed, EF-hand containing, Ca 2þ -binding protein that serves as the Ca 2þ -sensor for many cellular events (Gnegy 1993). All IP 3 R subtypes are inhibited by Ca 2þ -CaM Michikawa et al 1999;Missiaen et al 1999;Adkins et al 2000;Missiaen et al 2000), and CaM has been shown to restore Ca 2þ inhibition to purified IP 3 R Michikawa et al 1999;Nosyreva et al 2002). Yet, it has proven difficult to relate these functional effects of CaM to either its effects on IP 3 binding or to identified CaM-binding sites within IP 3 R. CaM inhibits IP 3 binding to IP 3 R1 in a Ca 2þ -independent manner (Patel et al 1997;Cardy and Taylor 1998), through a site that probably lies within the SD (Adkins et al 2000;Sienaert et al 2002).…”
Section: Regulation Of Ip 3 Receptors By Ca 2þ and Ipmentioning
confidence: 99%
“…CaM came to the scene as it was demonstrated to ubiquitously bind and regulate IP 3 R (29,(42)(43)(44). CaM pulldown assay was performed by incubating CaM-conjugated agarose with cell lysates of Jurkat or J.Vav1, respectively, or using plain agarose beads as a negative control.…”
Section: Vav1 Interacts With Calmodulin Via Ch Domain In a Camentioning
confidence: 99%